Nordic paths to modernity - Árnason, Jóhann Páll, 1940-; Wittrock, Björn (Berghahn Books, 2012)
Within the growing attention to the diverse forms and trajectories of modern societies, the Nordic countries are now widely seen as a distinctive and instructive case. While discussions have centred on the 'Nordic model' of the welfare state and its record of adaptation to the changing global environment of the late twentieth century, this volume's focus goes beyond these themes. The guiding principle here is that a long-term historical-sociological perspective is needed to make sense of the Nordic paths to modernity; of their significant but not complete convergence in patterns, which for som.